STUDY OF PAVEMENT STRUCTURE DESIGN BASED ON MANUAL FOR PAVEMENT DESIGN DGH 2013 - FADILLAH (NIM : 15010077), SOFIA
The design of the road is one of the factors that affect the pavement structure performance.Pavement struktural design methods are generally divided into two approaches, empirical and analytical.Empirical method is a method that is based on experience or testing that has been done.In testing, the correlation searched from related parameters. Analytical method was developed using a mathematical calculation of the exact response of the pavement structure to the axle loads. Structure of pavement design method is used in Indonesia adopted from other countries among which Metode Analisis Komponen (MAK) Bina Marga 1987 adopted from AASHTO 1972 revision 1983 with adjustments to IndonesiaÃ‚Â’s condition and Pt T-01-2002-B adopted from AASHTO 1993. These methods are based on an empirical approach.Currently, Indonesia is switching from an empirical approach to the analytical approach. It required a manual that can accommodate those needs. IndII, a cooperation agency of Indonesian Government and Australian Goverment, making a manual named Manual Desain Perkerasan Jalan Bina Marga 2013. Design obtained from Manual Desain Perkerasan Jalan Bina Marga 2013is an initial design derived from the design charts. The initial design should be checked against Pt T-01-2002-B. In use, Pt T-01-2002-B will help convince struktural adequacy and practicality of construction for load and climatic conditions in Indonesia.As a consequence, it is very important to control the elements of the design method in this manual when validating struktural adequacy.In this report, the validation is done by comparing the results of the design with other methods, MAK Bina Marga 1987 and Nottingham 1983.Use of Nottingham as a comparison as it is a method of using the analytical approach, the same as Manual Desain Perkerasan Jalan Bina Marga 2013.From the calculation, design according to Manual Desain Perkerasan Jalan Bina Marga 2013for all traffic load variations resulted in a total equivalent thickness is thicker than the other methods.